PENGARUH LITERASI FINANCIAL, FINANCIAL ATTITUDE, LOKASI DAN RELIGIUSITAS TERHADAP MINAT MENABUNG DI BANK SYARIAH (Studi Kasus Pada Masyarakat Desa Sirap Juai Kab. Balangan) - Zakiyah Zakiyah; Abdul Wahab (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2022)
The Islamic finance industry is one of the important elements in the implementation of development that plays a role in economic activity. However, the development of Islamic financial institutions must also be followed by the Islamic financial literacy of the community itself. Thus, someone will behave based on the level of knowledge and confidence in making decisions in choosing a financial institution as a financial intermediary, such as using banking services. This study aims to determine the effect of financial literacy, financial attitudes, location and religiosity on interest in saving in Islamic banks in the people of Sirap Juai Village, Kab. Balangan. The variables in this study were financial literacy (X1), financial attitudes (X2), location (X3), religiosity (X4) and interest in saving (Y) as measured by a Likert Scale. The population of this study is the entire community in Sirap Village. The sample in this study was taken randomly, namely the people of Sirap Village, amounting to 77 people. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive data analysis, validity data analysis, and hypothesis testing with the help of SPSS 25.0 for windows program. The results show that: 1) partially financial literacy, financial attitude, location and religiosity variables have a significant effect on interest in saving in Islamic banks. 2) There is a significant effect simultaneously (simultaneously) of the independent variable on the dependent variable with a calculated F value of 81.020 with sig. F = 0.000 (p < 0.05).